EVALUATION OF THE INFANTILE SELF-CONCEPT IN PRACTICANTS OF RHYTHMICAL GYMNASTICS (Fiep Bulletin - online, 2014)
The objective of the study was to evaluate the level of the infantile self-concept in children that practice Rhythmical Gymnastic between 5 and 6 years old. This research was characterized as a descriptive and case study research. The target population was composed by thirteen girls, chosen intentionally in the private school system, with the previous authorization of the school and the parents. As an instrument of measure, there has been used the Sánchez and Escribano (1999) test of Perception of the Infantile Self-Concept (PISC) in its individual form which consists in the presentation of thirty-four drawings. The data collection was made in the school before the time of practice of the Rhythmical Gymnastic. To analyze the data there have been used descriptive statistics. The results showed that the level of the self-concept in the children presented positive results in the four categories (autonomy, confidence, physical evolution and school world). Besides this, when these categories were compared in relation to the time of practice of the modality, there has been observed that in all of the categories the value of the levels in the self-concept were higher to the children that practiced the modality for more than one year. This way, it can be concluded that the infantile self-concept showed itself positive and in the construction process in some of the categories (autonomy and confidence), which will depend on the environment contexts and on the subjects that participate of this environments; and the sports practice showed itself as a positive element because the highest average was in the physical evolution category.
Keywords: self-concept; rhythmical gymnastic; children